LEGAL BASIS FOR ORGANIZING PHYSICAL EDUCATION AND SPORTS - Gilijova Arzigul Mametmiratovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses such issues as the modern policy of elite sports, the system of physical education in higher educational institutions, the role of physical education in the development of personality, the system of physical education in the country, as well as the main tasks of higher educational institutions for the preparation specialists.